2014
DOI: 10.1111/ijd.12603
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging in paraneoplastic autoimmune multiorgan syndrome: retrospective single site study and literature review of 225 patients

Abstract: Diagnostic imaging is frequently utilized in PAMS with unknown malignancy. Both conventional CT and 18F-FDG PET/CT are likely to detect the typical underlying neoplasms. Relative to conventional CT, 18F-FDG PET/CT may provide additional useful information regarding prognosis for the likely underlying malignancies, although there is a paucity of reports describing the use of this modality for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 152 publications
(270 reference statements)
1
13
0
Order By: Relevance
“…The clinical features of PNP include stomatitis, mucositis, and skin lesions. Furthermore, PNP is frequently associated with hematologic neoplasms, including non-Hodgkin lymphoma, chronic lymphocytic leukemia, and CD [21,22]. In this series of CD cases, 9 were considered to have PNP.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical features of PNP include stomatitis, mucositis, and skin lesions. Furthermore, PNP is frequently associated with hematologic neoplasms, including non-Hodgkin lymphoma, chronic lymphocytic leukemia, and CD [21,22]. In this series of CD cases, 9 were considered to have PNP.…”
Section: Discussionmentioning
confidence: 98%
“…PNP is associated with underlying neoplasms, the most frequent of which are hematologic malignancies. Previous studies revealed that non-Hodgkin lymphoma (about 40%) is the most frequent neoplasm, followed by Castleman disease (15~37%) and chronic lymphocytic leukemia (CLL) (7~18%) (10, 11, 20). Castleman disease has been reported as the most frequent neoplasm in Korea and China (21, 22), suggesting that the incidence of associated neoplasms vary by ethnicity.…”
Section: Disease Manifestationsmentioning
confidence: 99%
“…Given the fact that Castleman disease has an extremely low incidence in the general population, cases of PNP with Castleman disease are highly frequent. A minor fraction of neoplasms associated with PNP represents non-hematologic neoplasms, including neoplasms originating from the thymus (e.g., thymoma), sarcoma, malignant melanoma, and various epithelial-origin carcinomas (e.g., adenocarcinoma and squamous cell carcinoma) (10, 14, 20, 24, 25). Some cases of PNP were diagnosed before an underlying malignancy was detected (2628).…”
Section: Disease Manifestationsmentioning
confidence: 99%
“…In those without a prior diagnosis, workup often includes imagining. A recent analysis conducted at Mayo Clinic with 17 patients from their institution and 208 from a literature review suggested that 18 F-FDG PET/CT imaging was equal to CT in detecting malignancy; however, 18 F-FDF PET/CT was felt to better facilitate staging of lymphoma and guidance of subsequent biopsy procedures [60]. Prognosis is generally considered to be poor with mortality rates of 75-90 % quoted historically [61].…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%